2007
DOI: 10.1080/00480169.2007.36760
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the acute electroencephalographic responses of calves to noxious stimulus with scoop dehorning

Abstract: The results validate use of the EEG and a minimal anaesthesia model for assessment of noxious sensory inputs in cattle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 49 publications
9
75
0
1
Order By: Relevance
“…Significant increases in F50 and F95 were found during the first 10 s after decapitation. These are consistent with responses to noxious stimulation found in other studies 15,19,21,22 and can be interpreted as such. A significant and a gradual decrease in the Ptot was observed in the current study and was similar to the reductions in the power component of specific EEG frequency bands (1-100 Hz and 13-100 Hz) after decapitation of both conscious and anaesthetized rats reported in a recent study.…”
Section: Discussionsupporting
confidence: 81%
“…Significant increases in F50 and F95 were found during the first 10 s after decapitation. These are consistent with responses to noxious stimulation found in other studies 15,19,21,22 and can be interpreted as such. A significant and a gradual decrease in the Ptot was observed in the current study and was similar to the reductions in the power component of specific EEG frequency bands (1-100 Hz and 13-100 Hz) after decapitation of both conscious and anaesthetized rats reported in a recent study.…”
Section: Discussionsupporting
confidence: 81%
“…Others (e.g. Gibson et al, 2007 andMellor et al, 2009) state that the ventral neck cut is a noxious stimulus and that there is strong evidence that this cut would be perceived as painful from the time of the neck cut until loss of consciousness. Until now, neurophysiological methodology has not provided a final and definitive answer to this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results showed that EEG spectral analysis and MPF were useful methods for assessing manifestation of analgesia in various species [28][29][30][31][32]. Jang et al (2009) also found that SEF95 showed a strong correlation with the depth of anesthesia in rats.…”
Section: Discussionmentioning
confidence: 88%